Gene drives in malaria control: what we need to know - Mudziwapasi, Reagan; Changara, Munyaradzi Christopher; Ndudzo, Abigarl; Kaseke, Tinotenda; Godobo, Farai; Mtemeli, Floryn L.; Shoko, Ryman; Songwe, Fanuel; Ndlovu, Sakhile; Mlambo, Sibonani Sandra (Taylor & Francis Open Access, 2022)
Gene drives are being used to enhance a DNA sequence’s likelihood of passing between generations via sexual reproduction. Gene drives can be deployed to manipulate natural populations. They can be used to suppress populations by reducing the number of individuals in a population or to modify populations. There are more than 3000 mosquito species in the world, some of which are vectors of diseases. Malaria is a typical disease whose vectors are mosquitoes. It affects mostly tropical countries. It kills many people annually, many of whom are children. Interventions currently in use, such as indoor residual spraying and mosquito nets, are proving insufficient to eradicate malaria. Gene drives can be used in different ways to control mosquito populations or to eliminate mosquito species, thereby reducing malaria cases and deaths. This can occur through population replacement or suppression. However, before the elimination of any mosquito species for malaria control, it is necessary to consider the effects of such an action. Additionally, there is a need to review the options available for the control of mosquitoes and to create awareness of the benefits and risks of such an action. This paper, therefore, looks at the role of mosquitoes in the environment, the methods of controlling mosquitoes and malaria and necessary considerations when using gene drives inter alia.